Medium and Small Form. A Volume on the Long History of a Seemingly Young Genre (KULT_online, 2018)
Michael Gamper, Ruth Mayer and the contributors to Kurz and Knapp address the currently urgent quest for a poetics of brevity through a media-historical analysis of the small form since the 17th century. Instead of solely focusing on text messages, Twitter, Snapchat and Vine, the analysis covers early modern apophthegma, Nietzsche’s aphorisms and early cinema through to Twitter feeds and cell phone videos with a special focus on their medial embedding. The work breaks through the fixation on shortness to shed light on the respective practices involved in this form’s production as the origins of a poetics specific to the small form.